Pakan dari Limbah Kepala Udang dan Ampas Tahu untuk Pertumbuhan dan Kelangsungan Hidup Benih Ikan Patin - Latinulu, Atrila; Juliana, Juliana; Koniyo, Yuniarti (Fakultas Kelautan dan Teknologi Perikanan - Universitas Negeri Gorontalo, 2024)
The aim of the research was to determine the benefits of artificial feed using shrimp head waste and tofu dregs for the growth and survival of catfish (Pangasius sp) seeds. The method used was an experimental method using a Completely Randomized Design (CRD), with 5 treatments and 3 replications, namely treatment A (75% shrimp heads + 25% tofu dregs), treatment B (50% shrimp heads + 50% tofu dregs ), treatment C (25% shrimp heads + 75% tofu dregs), treatment D (100% shrimp heads) and treatment E (100% tofu dregs). The results of the Analysis of Variety Analysis (ANOVA) showed that the use of feed using shrimp head waste and tofu dregs had no effect on the growth and survival of catfish (Pangasius sp) seeds. The highest growth and survival was in treatment D (100% shrimp heads) and the lowest was in treatment E (100% tofu dregs).